Teaching Reading Comprehension through Cooperative Script to the Eighth Grade Students of the Private Junior High School Nurul Iman Palembang - Muhammad Ali Akbar Zam (Universitas PGRI Palembang, 2015)
AbstractThe main problem of this research was “Is it effective to teach reading comprehension through cooperative script to the eighth grade students of the Private Junior High School Nurul Iman Palembang?” Therefore, the objective of this research was to find out whether or not it was effective to teach reading comprehension through cooperative script to the eighth grade students of the Private Junior High School Nurul Iman Palembang. In this research, the writer used pre-experimental as a method of the research with one-group pretest-posttest design. The population of this research was all of the eighth grade students of the Private Junior High School Nurul Iman Palembang, which consists of 5 classes those were composed 171 students. As the sample, the writer took one class as the sample from the population by convenience non-random sampling. The class as sample of this study was VIII.E, numbers of the students were 36 students, for collecting the data the writer used written test with multiple-choice, and analyzed them by using matched t-test. The result of this research shows that, there were differences between students’ achievement in pre-test and pos-test. The mean score of the students in pre-test was 58.3 while the mean score of the students in post-test was 68.7. The result of matched t-test, the writer found it was 7.819; it was higher than t-table 1.689. It shows that the alternative hypothesis was accepted and the null hypothesis was rejected, so teaching reading comprehension through cooperative script to the eighth grade students of the Private Junior High School Nurul Iman Palembang was effective. Key Words: Teaching reading, Reading comprehension, and Cooperative script